MODERN PATHOGENETIC ASPECTS OF GESTATIONAL DIABETES MELLITUS - Андреева, Маргарита Викторовна; Заболотнева, Ксения Олеговна; Тугай, Екатерина Александровна (Mother and Baby in Kuzbass, 2024)
From the perspective of modern obstetrics, gestational diabetes mellitus is considered an epidemic of the 21st century. Hypeglycemia, which occurs as a consequence of impaired glucose tolerance and dysfunction of pancreatic β-cells, is the basis of the pathogenesis of this complication. Routine risk factors for the disease include overweight and obesity, late reproductive age, family history, and polycystic ovary syndrome. The long-term effects of GDM are the development of obesity, type 2 diabetes mellitus and cardiovascular pathology in both mother and child. Commonly accepted therapeutic measures for the management of such pregnant women are changes in lifestyle and nutrition, insulin therapy in the absence of effect from the above methods. The purpose of the lection is to systematize existing knowledge about the mechanisms of development of gestational diabetes mellitus in order to assess the possibilities of developing effective means of preventing its development and progression.
Keywords: gestational diabetes mellitus; risk factors; pathophysiology; review